Analysis of differential gene expression in stretched podocytes: osteopontin enhances adaptation of podocytes to mechanical stress - Endlich, Nicole; Sunohara, Masataka; Nietfeld, Wilfried; Wolski, Eryk W.; Schiwek, Daniel; Kränzlin, Bettina; Gretz, Norbert; Kriz, Wilhelm; Eickhoff, Holger; Endlich, Karlhans (The FASEB journal, 2002)
Glomerular hypertension is a major determinant advancing progression to end-stage renal failure. Podocytes, which are thought to counteract pressure-mediated capillary expansion, are increasingly challenged in glomerular hypertension. Studies in animal models of glomerular hypertension indicate that glomerulosclerosis develops from adhesions of the glomerular tuft to Bowman's capsule due to progressive podocyte loss. However, the molecular alterations of podocytes in glomerular hypertension are unknown. In this study, we determined the changes in gene expression in podocytes induced by mechanical stress in vitro (cyclic biaxial stretch, 0.5 Hz, 5% linear strain, 3 days) using cDNA arrays (6144 clones). Sixteen differentially regulated genes were identified, suggesting alterations of cell-matrix interaction, mitochondrial/metabolic function, and protein synthesis/degradation in stretched podocytes. The transcript for the matricellular protein osteopontin (OPN) was most strongly up-regulated by stretch (approximately threefold). By reverse transcriptase-polymer chain reaction, up-regulation of OPN mRNA was also detected in glomeruli of rats treated for 2.5 wk with desoxycorticosterone acetate-salt, an animal model of glomerular hypertension. In cultured podocytes, OPN coating induced a motile phenotype increasing actin nucleation proteins at cell margins and reducing stress fibers and focal adhesions. Intriguingly, additional OPN coating of collagen IV-coated membranes accelerated stretch-induced actin reorganization and markedly diminished podocyte loss at higher strain. This study delineates the molecular response of podocytes to mechanical stress and identifies OPN as a stretch-adapting molecule in podocytes.
Gesehen am 24.06.2022